The Conceptual Pattern of National Base of Veterans of Iran - Hojatollah Soleimani; Fatemeh Nooshinfard; Fahimeh Babolhavaeji (Tehran University of Medical Sciences, 2018)
Background and Aim: To understand veterans' needs and to make future generations familiar with the culture of self-sacrifice and martyrdom, we need a database to store information. The first step for designing a base is to provide a conceptual framework of the base. This study aims to provide a conceptual model to create the national base of veterans in Iran.  Materials and Methods: This research was conducted in a two-step, mixed approach. The first step was conducted using content analysis method (quantitative) and the second step using Delphi (qualitative) technique. Data collection tool was Excel 2016 software. With the help of Delphi technique, a researcher-made conceptual pattern was sent to the experts in three rounds. Based on their views, the final plan of national base of veterans was formed. Results: Among the main components, introduction to the war was removed, history of war changed to history of wars, link to links, other materials to other contents, art and war to war and art, and the sub-component of possibilities turned into the main component. Veterans' personal information turned into veterans' database that changed into subsidiary components of the martyrs / veterans / prisoners-of-war / warriors database. Conclusion: The main components of the conceptual pattern of national base of veterans of Iran include: home page, introduction, conflicts and operations, equipment, war zones, facilities, news, cemeteries of martyrs, veterans' rules, questions and answers, history of wars, war and art, veterans' database, archives, links, guide, contact with us, FAQs, other content, resources, about the base, search, map.